Electron trajectories in a realistic gyrotron resonator - Dumbrajs, Olgerts (Mathematical Modelling and Analysis, 1998)
Gyrotron is a special tube generating powerful radiowaves in the millimeter wave range. Gyrotrons are mainly used to heat nuclear fusion plasma, in order to induce controlled thermonuclear reactions on earth. In addition, they have found a wide utility in radars and the high‐temperature processing of materials. Differential equations describing gyrotron operation are analyzed from the mathematical point of view. Phase portraits of electron trajectories in realistic resonators are determined.First Published Online: 14 Oct 2010